The morality of unconventional force - Simpson, T (Routledge, 2016)
Are there moral limits on what spies may do? And if so, what are they? The task of this chapter is not to set out a list of prohibitions or requirements, at least not in the ﬁrst instance. Rather, it is to articulate and justify a moral framework that will result in such requirements. The framework faces the interesting and tricky problem that, for all practical purposes and with some limited exceptions, non-practitioners cannot identify any such list. Moreover, practitioners cannot do so non-mutably. One has to enjoy the epistemic privileges that come from currently being a spy in order to contribute. This is frustrating for philosophers who would like to exercise ex cathedra moral authority. But there is a more serious implication: the juridiﬁcation of policy for spies should be resisted. The conclusion for which I argue is well summarised in the following slogan: spies play by big boys’ rules. The framework that I defend does not apply only to spies; it also applies to other practitioners of unconventional force, such as special forces or cyber-spooks, who likewise enjoy the permissions and restrictions that come from rule-governed practices. This form of enquiry is important. The years since 9/11 have seen an increasing desire among policymakers to use unconventional force in pursuit of national security objectives. The reasons for this are various. There is an accepted practice of governmental denial when it comes to unconventional operations. Oversight procedures are not public. The organisations involved are more agile and more often able to avoid the media limelight. Most importantly, non-state actors now pose a degree of threat that was arguably not present in previous years, but war is neither a proportionate nor an eﬀective means by which to conduct operations against these targets. Indeed, some think that the human rights violations consequent on war are so serious that there is moral imperative to seek forcible alternatives in countering threats (Dill 2014, 2016). Yet the kinds of activities in which the CIA, in particular, has been engaged, such as waterboarding and extraordinary rendition, have raised signiﬁcant controversy. We lack a clear account of the morality of these practices in both popular and academic discourse. My argument proceeds as follows. I ﬁrst identify the kinds of activities in which I am interested. I then outline how existing views on the ethics of force have been taken to apply to espionage. In particular, the ad bellum and in bello strictures of Just War theory are readily taken to apply directly to spies. This approach is compelling given some currently widespread views about the ethics of force. The approach is mistaken, however, for it misconstrues the status of Just War principles. Rightly understood, at least some of these principles have compelling force because of their status as mutually beneﬁcial conventions. I then apply this view to espionage and other forms of unconventional force, outlining the tricky policy implications of my thesis.